EXPLORATION OF EURASIAN PRISON CHAPLAINS’ PSYCHOLOGICAL WELL-BEING TO RAISE THEIR JOB SATISFACTION - Ignatsson, Jan; Odiņa, Indra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article aims to attract the attention of policymakers, educators, business-affiliated bodies, and community to the psychological well-being of such prison staff members as chaplains whose job satisfaction will directly influence inmates’ rehabilitation and the health of the society in general. A phenomenological research was carried out in a non-profit organization Good News Jail and Prison Ministry whose mission is to provide spiritually mature, equipped, and motivated chaplains serving in 22 states, one American territory and 25 countries. The research sample was the participants of six Eurasian regions. The data were collected using interviews, diary notes and reports of stakeholder and problem tree analysis. The literature review and the gained data reveal a clear profile of what and who prison chaplains should be to guide prisoners towards their integration into society. It exposes both sides of the same system, known as penitentiary, as well as indicates problem solution strategies as well as requirements to maintain the work in line with trends in the branch. The research has brought repeatedly proved evidence that the complicity of “state of the art” calls for more attention from policymakers, educators, business-affiliated bodies, and states clearly that more research is necessary.